2004
DOI: 10.1111/j.1949-8594.2004.tb18000.x
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Learning Constructs, Shifts in Learning Constructs, and Their Relationship to Course Achievement in a Structured Inquiry, Yearlong College Physics Course for Life Science Majors

Abstract: This study investigated differences and shifts in learning and motivation constructs among male and female students in a nonmajors, yearlong structured inquiry college physics course and examined how these variables were related to physics understanding and course achievement. Tests and questionnaires measured students' learning approaches, motivational goals, selfefficacy, epistemological beliefs, scientific reasoning abilities, and understanding of central physics concepts at the beginning and end of the cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
145
2
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(164 citation statements)
references
References 27 publications
14
145
2
3
Order By: Relevance
“…Since the 1980s an abundance of research has shown that science self-efficacy, or confidence in one's own ability to complete the actions necessary to perform a task [7], is related to success in particular fields [8][9][10][11][12], as well as a predictor of the career choice an individual will make [10,[13][14][15][16]. A few researchers in physics education have also shown a link between physics self-efficacy and success [17][18][19]. Further, at Florida International University we have found that Modeling Instruction (MI) has a positive impact on self-efficacy [20].…”
Section: Introductionmentioning
confidence: 99%
“…Since the 1980s an abundance of research has shown that science self-efficacy, or confidence in one's own ability to complete the actions necessary to perform a task [7], is related to success in particular fields [8][9][10][11][12], as well as a predictor of the career choice an individual will make [10,[13][14][15][16]. A few researchers in physics education have also shown a link between physics self-efficacy and success [17][18][19]. Further, at Florida International University we have found that Modeling Instruction (MI) has a positive impact on self-efficacy [20].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have reported the benefits of inquiry-related teaching approaches, suggesting that these techniques foster students' understanding of scientific processes, scientific literacy, and critical thinking (Cavallo et al, 2004;Glasson and McKenzie, 1998;Haury, 1993) among other competencies. Inquiry-based teaching can also improve students' understanding of the scientific method and its strengths and weaknesses (Keller et.…”
Section: Introductionmentioning
confidence: 99%
“…Different research studies had shown that gender difference plays a vital role in acquisition of scientific concepts, for instance, a research claimed significant gender difference (Cavallo et al, 2004). In 1994, Fraser and Young found meaningful change in boys' success rate in biology when seen in the perspective of gender differentiation.…”
Section: Discussionmentioning
confidence: 99%